Optimal design of label-free silicon “lab on a chip” biosensors - Zhang, Yaping (Elsevier, 2013)
This paper reported the optimal design of label-free silicon on insulator (SOI) “lab on a chip” biosensors. These devices are designed on the basis of the evanescent field detection principles and interferometer technologies. The well-established silicon device process technology can be applied to fabricate and test these biosensor devices. In addition, these devices can be monolithically integrated with CMOS electronics and microfluidics. For these biosensor devices, multi-mode interferometer (MMI) was employed to combine many stand-alone biosensors to form chip-level biosensor arrays, which enable real-time and label-free monitoring and parallel detection of various analytes in multiple test samples. This sensing and detection technology features the highest detection sensitivity, which can detect analytes at extremely low concentrations instantaneously. This research can lead to innovative commercial development of the new generation of high sensitivity biosensors for a wide range of applications in many fields, such as environmental monitoring, food security control, medical and biological applications.